Estimated prevalence of smallpox vaccine contraindications in Israeli adolescents. Issue 29 (17th June 2016) - Fogel, Itay; Brosh-Nissimov, Tal; Vager, Granit; Aviv, Yaron; Kassirer, Michael
Highlights: Replicating smallpox vaccines have the potential for serious adverse events. Only a small percentage of adolescents cannot receive the replicating vaccine. The main contraindication is active skin disorders. The prevalence of vaccine-excluded adolescents has increased over 16 years. Herd immunity and new-generation vaccines are options for susceptible populations. Abstract: Background: Routine smallpox vaccination for military recruits was discontinued in Israel in 1996. However, Israeli guidelines recommend post-event mass-vaccination. This study aimed to estimate the rate of Israeli adolescents at risk of severe adverse events after vaccination during 1998−2013. Methods: The study population included adolescents screened before military service in 1998−2013. Medical parameters correlating with contraindications to smallpox vaccination were retrieved from army databases, and were categorized by severity according to the Israeli post-event strategy. Results: Of 1, 180, 964 individuals, 1.86% had vaccination contraindications in a post-event scenario. An additional 1.24% had contraindications in a pre-event scenario. There was an increase in the percentage of contraindications over time, attributed to the rising incidence of atopic-dermatitis. Conclusions: Only a small percentage of the adolescent population is ineligible to receive the smallpox vaccine currently in use. This group may be protected by herd-immunity, or by new-generation vaccines designed to prevent severe adverse events.